HOW CASSIA ALATA L AFFECTS BLOOD GLUCOSE LEVELS IN DIABETES MELLITUS PATIENTS? - Sabrina Salsabilah; Mustika Sari; Muthmainnah J. Abdullah; said Kurniati; Emy Izzati; I Putu Sudayasa (SABDA EDU PRESS (SEP), 2024)
Candle bush (Cassia alata L.) are plants that are rich in antioxidants. There have been many studies that discuss the efficacy of Candle bush (Cassia alata L.) in skin diseases, but there is still less research that discusses the potential of Candle bush leaves as antidiabetics. Therefore, researchers want to test the effectiveness of Candle bush leaves (Cassia alata L.) in improving blood glucose levels (antidiabetic) using experimental animals (Rattus norvegicus strain wistar) induced with Streptozotosin (STZ). Candle bush leaf extract (Cassia alata L.) was made with maceration method using ethanol 70% solution. Experimental animals were divided into 6 groups. Group 1,2, and 3 are the control group, Group 4,5, and 6 are the groups that are given the extract with different doses each. This study proves that extract of Candle bush leaf (Cassia alata L.) can improve blood glucose levels of the experimental animals (Rattus norvegicus strain wistar).